Armed National Resistance Units – the Medium of the Games of the SSSR/Latvian SSR and Great Britain Special Operative Services in 1945–1956 - Vasilevskis, Janis (Genocidas ir rezistencija, 1997)
There are very few documentary sources on the activities of the KGB of the Latvian SSR during the period when the KGB organs of the Baltic republics were playing operative games with the intelligence services of Sweden and Great Britain. Based on the available sources, it is possible to give a general outline of the methods of KGB’s operations of the Latvian SSR.
Keywords: Latvia; Great Britain; intelligence; armed resistance; KGB